Antioxidant Activity and Hypoallergenicity of Egg Protein Matrices Containing Polyphenols from Citrus Waste - María Victoria Gil; Nuria Fernández-Rivera; Gloria Gutiérrez-Díaz; Jorge Parrón-Ballesteros; Carlos Pastor-Vargas; Diana Betancor; Carlos Nieto; Pedro Cintas (Antioxidants)
This study reports on the interactions of egg proteins, which represent a major health concern in food allergy, with polyphenols obtained from orange and lemon peels. The antioxidant properties of such citrus peel extracts prior to protein binding were evaluated. The resulting edible, and therefore inherently safe, matrices exhibit reduced IgE binding compared to pure proteins in indirect immunological assays (ELISA) using individual sera from patients allergic to ovalbumin and lysozyme. The reduced allergenicity could arise from the interactions with polyphenols, which alter the structure and functionality of the native proteins. It is hypothesized that the anti-inflammatory and antioxidant properties of the polyphenols, described as inhibitors of the allergic response, could add immunomodulatory features to the hypoallergenic complexes. A docking analysis using lysozyme was conducted to scrutinize the nature of the protein–polyphenol interactions. An in silico study unravelled the complexity of binding modes depending on the isoforms considered. Altogether, the presented results validate the antioxidant properties and reduced allergenicity of polyphenol-fortified proteins. Lastly, this study highlights the upgrading of vegetable wastes as a source of natural antioxidants, thus showing the benefits of a circular economy in agri-food science.